Students’ Satisfaction on School Services in a State College in the Philippines - Patalinghug, Mark Erana; Hortilano, Joan; Repaso, Ernil; Mollona, Angel; Patalinghug, Haidee Fuentes (Jurnal Pendidikan Progresif, 2021)
Abstract: Students’ Satisfaction on School Services in a State College in the Philippines. Objective: This study was purposely conducted to determine the satisfaction level of Bachelor of Science in Criminology students on the school services offered in J.H. Cerilles State College (JHCSC), Philippines in 2019. Methods: This is a descriptive type of research utilizing a modified-validated questionnaire from the working guide of the accreditors in the Accrediting Agency of Chartered Colleges and Universities in the Philippines, Inc. (AACCUP). Frequency Counts, Percentage, and Weighted Average Mean were used in analyzing the data. Total enumeration was used as the sampling methodology. A total of 152 criminology students were identified as the respondents of the study. Findings: Results show that library and guidance services have the highest level of satisfaction rating while school canteen and criminology laboratory have the lowest students’ satisfaction. Conclusion: The students were satisfied with the services offered by those offices that directly attended to their academic and emotional needs. Keywords: students satisfaction, school services, services quality, higher education institution. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202103